Human Erysipelothrix rhusiopathiae infection via bath water – case report and genome announcement - Zautner, Andreas E.; Tersteegen, Aljoscha; Schiffner, Conrad-Jakob; Ðilas, Milica; Marquardt, Pauline; Riediger, Matthias; Delker, Anna Maria; Mäde, Dietrich; Kaasch, Achim J. (Frontiers in Cellular and Infection Microbiology, 2022)
Erysipelothrix rhusiopathiae is a facultative anaerobic, environmentally stable, Gram-positive rod that causes swine and avian erysipelas as a zoonotic pathogen. In humans, the main manifestations described are circumscribed erysipeloid, generalized erysipeloid, and endocarditis. Here, we report a 46-year-old female patient who presented to the physician because of redness and marked functio laesa of the hand, in terms of a pain-related restricted range of motion, and was treated surgically. E. rhusopathiae was detected in tissue biopsy. The source of infection was considered to be a pond in which both swine and, later, her dog bathed. The genome of the isolate was completely sequenced and especially the virulence as well as the antimicrobial resistance genes, in particular the multiple sugar metabolism regulator (MsmR), and the vancomycin resistance locus (vex23-vncRS) were investigated in more detail.